Peranan Pengetahuan Bahasa, Budaya dan Implikasinya terhadap Pembelajaran Public Speaking Mahasiswa Bima - Rosadi, Ariani; Hermanto, Lubis (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
In recent years, the challenges of the disruptive era should be a positive impact on society, especially on young generations. It is necessary to improve language skills and adapt to the wider community, including its culture, especially for Bimanese students, West Nusa Tenggara. Therefore, this study aims to identify the role of language, cultural knowledge, and its implications for public speaking learning of Bimanese students of the communication science study program, Mbojo Bima College of Social and Political Sciences (STISIP) Mbojo Bima. The students involved in this study were in the fourth semester and the research method was ethnographic research. It is a qualitative research approach that allows the researcher to engage as participant-observation. Data were collected through observation, in-depth interviews, and video among ten Bimanese students. The informants originally came from Bima. The results of this research show that: (a) for Bimanese students, language and culture play a vital role in creating and maintaining communication. They use Bahasa Indonesia in formal context in which the audience comes from different cultures. However, some chose to mix Indonesian (official language) and Mbojo language (Local language) for audiences from the same culture, old people and less educated people as the proper way to respect them; (b) language and culture are inseparable parts and influential to the individuals’ ways of thinking and also how they describe the world or realities in the coordinate relationship and (c) Bimanese students could identify subordinate relation involved in learning about aspects of linguistics and ethic of language during public speaking learning.